If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(7 + -2b) + 2(5b + 2) = 0 (7 * 8 + -2b * 8) + 2(5b + 2) = 0 (56 + -16b) + 2(5b + 2) = 0 Reorder the terms: 56 + -16b + 2(2 + 5b) = 0 56 + -16b + (2 * 2 + 5b * 2) = 0 56 + -16b + (4 + 10b) = 0 Reorder the terms: 56 + 4 + -16b + 10b = 0 Combine like terms: 56 + 4 = 60 60 + -16b + 10b = 0 Combine like terms: -16b + 10b = -6b 60 + -6b = 0 Solving 60 + -6b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -6b = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -6b = 0 + -60 -6b = 0 + -60 Combine like terms: 0 + -60 = -60 -6b = -60 Divide each side by '-6'. b = 10 Simplifying b = 10
| 0.90x+0.05(20-x)=0.10(27) | | 0.000054A+0.015B+0.0036C=0 | | .585X+X=450 | | -10.1=w | | 1x+5-8x=26 | | 6500=20x*.30 | | -6n=11-5n | | -3-5n-6=6 | | 5(x+6)=14 | | -2(6a+4b)=24c | | 504-4-14=0 | | -11x+4=x+ | | 4.3461A+0.95613B+4.5455C=0 | | 5x=12x-14 | | 2-(6x-25)=7(x-2) | | 3x-4-3x+38=4x+2 | | h+7.9=1.3 | | 3(4+a)=6 | | 5n=11-6n | | 6-3x=-3x+ | | 2r(4r+8)-5r(6r-10)= | | 4a+2b+c=2 | | 2t^2+14t-3=3 | | 4x^2-36=g(x) | | a+24=62 | | -7=-5y+-4y+36-49+-21 | | h+8h= | | -5(x-11)=-95 | | r-9r= | | X+9x+18=0 | | 5+k-3=-3 | | -7=-5y+-4y+36-44+-21 |